Three Decades of Outcomes in Pediatric Inborn Errors of Immunity in a Middle-Income Setting: Survival by IUIS Class and the Role of HSCT - Chanunchida Watcharaporn; Usanarat Anurathapan; Suradej Hongeng; Samart Pakakasama; Wasu Kamchaisatian; Watcharoot Kanchongkittiphon; Wiparat Manuyakorn (Journal of Clinical Immunology, 2026)
Abstract Inborn errors of immunity (IEI) comprise a heterogeneous group of inherited disorders associated with substantial morbidity and mortality, yet long-term outcome data from middle-income countries remain limited. We conducted a retrospective cohort study of 123 children diagnosed with IEI at a tertiary referral center in Thailand between 1991 and 2022 to characterize clinical features, treatment, and survival. Patients were retrospectively classified according to the 2022 International Union of Immunological Societies classification. Kaplan–Meier and Cox proportional hazards analyses were performed to evaluate survival and factors associated with mortality. Predominantly antibody deficiencies were the most common IEI category (40.7%), whereas severe combined immunodeficiency was the most frequent individual diagnosis. Genetic confirmation was obtained in 46.3% of patients, and 19 (15.4%) underwent hematopoietic stem cell transplantation (HSCT). Overall mortality was 31.7%, with infection remaining the leading cause of death. Survival differed substantially across IEI classes, with the poorest outcomes observed in combined immunodeficiencies and the most favorable survival in predominantly antibody deficiencies. Among patients with severe transplant-eligible IEI, exploratory analyses demonstrated improved survival following HSCT. In multivariable Cox analysis, both haploidentical HSCT (adjusted hazard ratio [aHR] 0.10, 95% confidence interval [CI] 0.03–0.33) and matched related donor HSCT (aHR 0.01, 95% CI 0.001–0.10) were independently associated with lower mortality than non-transplant management. Male sex and combined immunodeficiency were independently associated with increased mortality. These findings demonstrate marked heterogeneity in outcomes across pediatric IEI and support earlier diagnosis, expanded molecular testing, timely referral, and greater access to HSCT to improve survival in resource-constrained settings.